The Innovation of Traditional Education System in Islamic Boarding Schools Based on Modernization - M. Chozin Machmud (Ilomata International Journal of Social Science, 2020)
This study aims to determine the form of innovation in the traditional education system of Islamic boarding schools which have adapted to become modern Islamic boarding schools. This study uses a qualitative research approach where qualitative research is the scientific method. The data collection technique uses participatory observation, in-depth interviews, the data analysis process begins by examining all available data from various sources. From the results of the analysis, the author can conclude that the innovation system of the Ar-Risalah Tegal Panjang Cariu boarding school in Bogor is quite different from other boarding schools in Indonesia, because the curriculum is quite strict. All students must follow all educational regulations, must be disciplined and obedient. Because the Ar-Risalah Tegal Panjang Cariu Bogor boarding school curriculum combines traditional education systems with modern education systems. The implication is a form of education in modern boarding schools that are responsive to the demands of the coming era which includes two aspects, universal and national. So that was found a boarding school that has a true cultural identity that is a new Indonesia that the universality of Islam is able to give birth to a future Indonesian society that is religious.